Mixed-phase MoS2 nanosheets anchored carbon nanofibers for high energy symmetric supercapacitors. (July 2023) - Kour, Pawanpreet; Deeksha,; Kour, Simran; Sharma, A.L.; Yadav, Kamlesh
Abstract: Mixed-phase MoS2 (MS) nanosheets anchored carbon nanofibers (CNFs) have been synthesized via a hydrothermal route. The concentration of CNFs has been varied in the MS/CNF-x composite (where, x = 1, 1.5, 2, and 3 represents the molar concentration of CNFs) to investigate the impact of CNFs on the electrochemical behavior of the material. The incorporation of CNFs offers a conductive path for the diffusion of ions and provides structural support which limits the restacking of the MoS2 layers during the charging/discharging. The MS/CNF-2 composite delivered superior electrochemical performance compared with the other composites owing to the positive synergy between MoS2 and CNFs. The specific capacitance manifested by MS/CNF-2 (626.08 F g −1 at 1 A g −1 ) is about four times that of pristine MS (159.35 F g −1 ). It is also observed that MS/CNF-2 exhibited higher electrochemical stability than pristine MS. Furthermore, the symmetric supercapacitor (SSC) device achieved a tremendous energy density of 42.6 Wh kg −1 at 2.4 kW kg −1 . To test its practical applicability, LEDs of different color (red, green, and blue) have been illuminated using a series combination of three symmetric electrode cells. The red, green, and blue LEDs lighted up for 15 mins, 7 mins, and 3 mins. The results demonstrate the superiority of the MS/CNF composite for symmetric supercapacitors. Graphical abstract: Unlabelled Image Highlights: Mixed-phase1T-2H MoS2 nanosheets anchored carbon nanofibers have been synthesized via a hydrothermal route. The electrochemical performances of MS/CNF-x composites have been tested in a symmetric configuration. MS/CNF-2 manifested a high capacitance of 626.88 F g -1 at 1 A g -1, almost 4 times the pristine MS. The symmetric supercapacitor (SSC) device achieved a high energy density of 42.6 Wh kg -1 at a power density of 2.4 kW kg -1 . The practicality of SSC device has been tested by glowing red, green, and blue LEDs.